2021
DOI: 10.3390/s21113674
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and Transparent Polymer-Based Optical Humidity Sensor

Abstract: Thin spin-coated polymer films of amphiphilic copolymer obtained by partial acetalization of poly (vinyl alcohol) are used as humidity-sensitive media. They are deposited on polymer substrate (PET) in order to obtain a flexible humidity sensor. Pre-metallization of substrate is implemented for increasing the optical contrast of the sensor, thus improving the sensitivity. The morphology of the sensors is studied by surface profiling, while the transparency of the sensor is controlled by transmittance measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In recent years, flexible and wearable sensing devices have been of great interest due to their unique characteristics such as portability, endurance, light weight and the combination with the IoT environment-monitoring concept [ 82 , 83 ]. Another superior characteristic of polymer-based humidity sensors is compatibility with other sensing materials.…”
Section: Humidity Nanosensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, flexible and wearable sensing devices have been of great interest due to their unique characteristics such as portability, endurance, light weight and the combination with the IoT environment-monitoring concept [ 82 , 83 ]. Another superior characteristic of polymer-based humidity sensors is compatibility with other sensing materials.…”
Section: Humidity Nanosensorsmentioning
confidence: 99%
“…Another superior characteristic of polymer-based humidity sensors is compatibility with other sensing materials. By integrating a sensing material onto a polymer substrate such as cellulose [ 84 , 85 , 86 , 87 , 88 , 89 , 90 ] or PET [ 82 , 91 ] using the PVD, CVD or solution methods, it is able to enable the high-strength materials to achieve flexible characteristics. Table 2 lists several different sensing materials with polymer-based substrates [ 82 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ].…”
Section: Humidity Nanosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic range is 40%RH–80%RH. Katerina Lazarova et al [ 195 ] reported the use of amphiphilic poly(vinyl alcohol-co-vinyl acetal) copolymer, where a gold or palladium layer is deposited onto a flexible substrate such as polyethylene terephthalate, followed by spin coating polymer overlayer. The functional composite coating swells in response to increasing RH and changes the transmittance of light.…”
Section: Literature and The State-of-the-artmentioning
confidence: 99%
“…Up to now, many different transduction methods have been explored, including capacitance [ 5 ], resistance [ 6 ], optical fibers [ 7 ], field effect transistors [ 8 ], and quartz crystal microbalance [ 9 ]. Many materials have been explored as humidity sensing layers to develop devices displaying high sensitivity, a good linear range, a fast response, and fast recovery times, such as carbon nanotubes [ 10 ], metal oxides [ 11 ], polymers [ 12 ], and graphene-like materials [ 13 ]. Among graphene-like materials, graphene oxide (GO) has been one of the most investigated materials.…”
Section: Introductionmentioning
confidence: 99%